PENGARUH MOTIVASI, KEMAMPUAN KERJA DAN FASILITAS KERJA TERHADAP KINERJA PEGAWAI DI KANTOR PELAYANAN PAJAK PRATAMA MEDAN PETISAH - Hery Irwansyah Sinaga (JRAM (Jurnal Riset Akuntansi Multiparadigma), 2020)
The formulation of the problem in this research is how the influence of motivation on employees  performance. How  influence of work ability on employees  performance. How  influence of  work facility on employees  performance. How  influence of  motivation, work ability and  work facility on employees  performance. The purpose of this research is for know influence and analize of  motivation on employees  performance. For know influence and analize of work ability on employees  performance. For know influence and analize  work facility on employees  performance. For know influence and analize motivation, work ability and  work facility on employees  performance.  The sample in this research is 88 employees, with data analysis technique used is multiple linear regression analyze. The results of this research explain that motivation effect has a positive and significant on employee  performance. Work ability effect has a positive and significant on employee  performance.  work facility effect has a positive and significant on employee  performance. Motivation, work ability and  work facility effect  have a positive and significant on employee  performance